Attitudes and Practices of Homeowners in the Decision-making Process for Building Energy Renovation. (2017) - Abreu, Maria Isabel; Oliveira, Rui; Lopes, Jorge
Abstract: The most recent studies point out that building users play a critical role in the decision-making process for the energy renovation of buildings as well as in energy use during the building life-time occupancy. Nevertheless, this important player has been poorly considered in the policies implemented. The homeowner, whose role has been passively induced to renovate accordingly with impositions of the regulations, is calling for himself a more active participation in the renovation process. The social dimension of the building renovation has been ignored. This study aims to highlight the role of the homeowner in the decision-making for energy building renovation investigating his motivations, needs, attitudes and daily routines. A selected group of Portuguese homeowners were interviewed. Also in Portugal, homeowners' qualitative decisions and everyday life practices have a strong influence in the decision-making for building renovation.